2015
DOI: 10.3329/jesnr.v8i1.24660
|View full text |Cite
|
Sign up to set email alerts
|

Status of Water Quality in the Tista River at Kaunia Point and its Impact on Aquatic Environment

Abstract: The study was conducted to investigate the surface water quality of the Tista River at Kaunia point in wet (September to November) and dry season (December to February) during the period from September 2013 to February 2014. The water samples were collected from five different sampling stations of Tista River mentioned as Station 1 (St-1), 2 (St-2), 3 (St-3), 4 (St-4) and 5 (St-5). The analysis of the study showed that the average transparency was 13.28 and 32.31 cm in wet and dry season, respectively, while t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 3 publications
4
24
3
Order By: Relevance
“…A total of 50 respondents who are directly and indirectly dependent on the river for their livelihood were surveyed from the study area. (Islam et al 2015a), which are mostly similar to the present study. Yasmeen et al (2012) found that the temperature of Buriganga River water in dry season complies with standard, which was found around 21.9 to 22.4°C; whereas in wet season, it was around 31 to 33°C, exceed the standard limit (20 to 30°C) set by DoE (2016).…”
Section: Social Surveysupporting
confidence: 93%
“…A total of 50 respondents who are directly and indirectly dependent on the river for their livelihood were surveyed from the study area. (Islam et al 2015a), which are mostly similar to the present study. Yasmeen et al (2012) found that the temperature of Buriganga River water in dry season complies with standard, which was found around 21.9 to 22.4°C; whereas in wet season, it was around 31 to 33°C, exceed the standard limit (20 to 30°C) set by DoE (2016).…”
Section: Social Surveysupporting
confidence: 93%
“…The mean values of temperature, pH, TDS, EC were higher but DO, BOD were lower of the present study than the Buriganga river (Hasan et al, 2009). Islam et al (2012) investigated that temperature, TDS, EC were higher but pH, DO were lower in Dhaleshwari river than present study. Alam et al (2007) found the mean values of pH, DO, BOD and COD lower in the Surma river than the present study.…”
Section: Physico-chemical Characteristics Of River Water and Sedimentcontrasting
confidence: 56%
“…Islam et al [23] found DO ranged from 4.9 to 9.0, 4.1 to 9.8 and 5.7 to 7.3 mg/l respectively in monsoon, post-monsoon and pre-monsoon seasons and the samples were collected between 9:30-11:30 am. The main causes of lower DO value in the present study were the presence of organic matter in the water body, lack of sunlight in the morning (7.30-8.30 am), nutrients from induced fertilizers, human activities and other animal wastes.…”
Section: Physicochemical Parametersmentioning
confidence: 99%